Connected Readers: Reading Networks and Community in early twentieth-century New Zealand - Liebich, Susann (Mémoires du livre / Studies in Book Culture, 2010)
Drawing on the archive of Fred Barkas (1854-1932), a middle-class New Zealand reader, the article explores how reading networks within local communities were established and how, where and when readers connected to other readers to form a local reading community. Barkas’ letters reveal an often unorganised and diffuse reading culture in Timaru, NZ, which was highly social and defined along such markers as social status and cultural capital. Readers connected in a variety of ways, interwoven into other activities within the local community and in spaces not traditionally associated with reading. The article concludes by asking how readers in New Zealand were also connected to other reading communities around the British World and formed part of a global reading community.